Broad-spectrum resistance and susceptibility to bacterial blight and bacterial leaf streak of rice - Bossa Castro, Ana M.; Tekete, Cheick; Raghavan, Chitra; Delorean, Emily E.; Dereeper, Alexis; Verdier, Valerie M.; Dagno, Karim; Koita, Ousmane; Mosquera Cifuentes, Gloria Maria; Leung, Hei; Leach, Jan E. (2018)
Quantitative trait loci (QTL) that confer broad-spectrum resistance (BSR) have been elusive targets of crop breeding programs. Bacterial leaf streak (BLS) and bacterial blight (BB), caused by Xanthomonas oryzae pv. oryzicola (Xoc) and Xanthomonas oryzae pv. oryzae (Xoo), respectively, are responsible for major losses in rice production in Asia and Africa. Controlling these two diseases is particularly important in Sub-Saharan Africa, where no sources of BSR are available in currently deployed varieties. Our goal is to identify novel, broad-spectrum resistance sources to control BLS and BB in rice, using a Multi-parent Advanced Generation Inter-Cross (MAGIC) population, derived from eight elite indica cultivars. MAGIC populations have an increased level of recombination and provide higher precision and resolution to detect QTL. The MAGIC parents and lines were genotyped and phenotyped in both greenhouse and field conditions by screening with diverse strains of Xoc and Xoo. Using genome-wide association and interval mapping analysis, we identified 37 strain-specific QTL, and 14 QTL effective against multiple X. oryzae strains. From these, three QTL are pathovar-specific and 11 confer resistance to both pathovars. By detecting phenotypic effects of causal alleles, we have identified resources that will facilitate a better understanding of how the involved genes contribute to resistance or susceptibility. Because the MAGIC founders are elite varieties, the BSR QTL identified can be rapidly incorporated into breeding programs to achieve more durable resistance to BLS and BB.